KENDALA PENINGKATAN KEMAMPUAN LITERASI NUMERASI BERBASIS PERMAINAN TRADISIONAL DI SDN PLOSOKEREP 2 BLITAR - Aurila Putri Marhaeni; M. Anas Thohir (Jurnal Karya Pendidikan Matematika, 2022)
The existence of the Covid-19 pandemic has become a threat to the education of the nation's future successors which is also exacerbated by the swift currents of globalization. Numerical literacy is one of the important literacy skills to be mastered by elementary school students. Especially if numeracy literacy learning is supported by traditional game media. This study aims to determine the obstacles in increasing traditional game-based numeracy literacy skills at SDN Plosokerep 2 Blitar. as for the research method used is qualitative research with the type of case study. This research was carried out at SDN Plosokerep 2, especially for grade 2 students